Mechanical Properties of Burnished Steel AISI 1008 - Kadhim, Zeyad D.; Abdulrazzaq, Mohammed Abdulraoof; Hussain, Wassan Suheil (Al-Khwarizmi Engineering Journal, 2018)
Burnishing improves fatigue strength, surface hardness and decrease surface roughness of metal because this process transforms tensile residual stresses into compressive residual stresses. Roller burnishing tool is used in the present work on low carbon steel (AISI 1008) specimens. In this work, different experiments were used to study the influence of feed parameter and speed parameter in burnishing process on fatigue strength, surface roughness and surface hardness of low carbon steel (AISI 1008) specimens. The first parameter used is feed values which were (0.6, 0.8, and 1) mm at constant speed (370) rpm, while the second parameter used is speed at values (540, 800 and 1200) rpm and at constant feed (1) mm. The results of the fatigue test showed that improvement in fatigue limit, where the highest fatigue limit was obtained at (1mm feed, 1200rpm speed) in burnishing process which was (169 Mpa). The hardness results, showed increasing feed and speed values lead to increasing the hardness. The burnishing process reduces surface roughness by producing accurate and better surface finish. The best surface fineness of metal at (1mm feed and 1200 rpm speed) was 0.11 μm.